Modeling the factors causing cost overrun in UAE construction industry - Ahmed Marey Alhammadi, Ahmed Salem (2022)
Construction industry is facing a serious issue of cost overrun throughout the world. In UAE also, this is the crucial issue which is resulted from several factors. For successful construction projects, it is imperative to understand and control the factors causing overrun of the cost. Hence, this study developed a graphical model representing the factors affecting the cost overrun in the UAE construction projects. The study adopted a quantitative approach and collected the through the questionnaire survey and analysed with Partial Least Square Structural Equation Modelling (PLS-SEM) approach using SmartPLS software. Initially, a pilot study was conducted to verify the 27 factors identified from literature and classified into five groups. A panel of 33 experienced construction practitioners confirmed the relevancy of the identified factors with construction industry of the UAE. However, they suggested reforming the groups into three categories. A survey was done by distributing 200 questionnaires where only 116 valid responses were received back. The factors were ranked using average index score as well as PLS-SEM model of factors affecting the cost overrun was developed with SmartPLS software. PLS-SEM involved 4 iterations before the model achieved the measurement evaluation criteria adequacy. The model was evaluated based on hypothesis testing, coefficient of determination, effect size, predictive relevancy and goodness-of-fit (GoF). The results of the criteria evaluations showed that the structural component of the model has achieved the threshold values of the criteria. The overall GoF value of the model was 0.338 which indicates that the model is having medium validating power in explaining the relationship of factors in affecting the cost overrun in UAE construction industry. The model outcomes were verified through interview by seven experienced construction experts. All the seven experts agreed with the ranking in the context of their experiences in handling construction projects in UAE. This model highlights the most influencing factors which cause cost overrun based on the interdependence between the factors. It means controlling critical factors will be helpful in controlling the other factors also. Overall, this model can benefit the practitioners in controlling the cost overrun run issue in the UAE construction industry.